Validity of testing and training using the kayak ergometer - Zanevskyy, I. P.; Chodinow, W.; Zanevska, L. h. (Pedagogics, psychology, medical-biological problems of physical training and sports, 2019)
Background and Study Aim. The paper is dedicated to the problem of the strength testing and training using the ergometer rowing performance in the flat water kayak sport. The aim of the research was to create a model of validity based on the relationship between the ergometer and on-water performance competition rowing. Material and Methods. Nineteen 15-17 years old male kayak rowers during the off-season were randomly divided into two groups. An experimental group trained according the same program as the control group, but two times a week a part of the common strength training exercises was substituted with a high-intensity strength training using the ergometer rowing. A whole amount of strength loading on all the rowers of the two groups was equal. Validity of testing and training of the ergometer rowing in the kayak sport was evaluated using interclass correlation between competition performance on 500 m on-water kayak and ergometer rowing. Results. Strong significant correlation is revealed between competition performance of on-water kayak and ergometer rowing before and after the off-season (| r | = 0.892, 0.902, p <0.001), that shows rather good validity. Other result of the correlation analysis shows good prognostic ability of the ergometer performance regarding competition performance of on-water kayaking (| r | = 0.913). Conclusions. The proposed model based on the relationship between the ergometer and on-water performance competition rowing shows rather good validity of the strength testing and training in the on-water kayak sport.